LO19: Introduction of a regional interactive group supervision tool to maximize multi-program research project support. (15th May 2017) - Atkinson, P.R.; Magee, K.; Carter, A.; Hurley, K.F.; Sibley, A.; Watson, M.; Urquhart, D.; DeMone, C.; Fitzpatrick, E.; Fraser, J.; French, J.; Howlett, M.; et al.
Abstract : Introduction/Innovation Concept: University Departments of Emergency Medicine are responsible for the supervision of research and other scholarly projects for fellows, residents and students, though often lack resources to provide adequate input and oversight. Many departments cover large geographical areas and several programs. We piloted new research committee structures and processes to improve oversight and output of research projects.Methods: We created an interactive group supervision tool based around formation of a collaborative research committee, with rotating chairs from each program, to provide supervision and face to face interaction, and direction for research learners. Included were all Dalhousie University adult and pediatric emergency medicine residency and fellowship programs, as well as trauma and EMS programs across Nova Scotia, New Brunswick, and Prince Edward Island. In addition to providing expertise in clinical trial coordination, database management, research administration, grant applications and Research Ethics Board submissions, we have completed a 2-year pilot of our interactive group supervision tool for research projects.Curriculum, Tool, or Material: The interactive tool consists of a structured PICOD form; allocation of topic and research mentors; standardized yearly milestones from project development through presentation and publication; and regular video-conferenced and in-person interactive group sessions involving several project leads, as well as program research directors, researchers, and co-ordinators. To date, all participating program learners have engaged with the tool, with positive feedback from learners, supervisors and program directors.Conclusion: We report our development of a regional collaborative interactive group supervision tool, that maximizes expert resources in the provision of research and scholarly project supervision.